Profile of Prophylactic Antibiotics in Cesarean Sections with Occurrence of Infection: Literature Review - Asfarina, Hairunnisyah; Zulkarnain, Bambang Subakti (Eduvest - Journal of Universal Studies, 2025)
Caesarean section is a surgical procedure that requires the use of prophylactic antibiotics throughout its implementation. Providing prophylactic antibiotics before surgery can reduce the risk of postoperative infections. The most common short-term complications of a caesarean section are wound infections. This research aims to ascertain the profile of prophylactic antibiotic use in caesarean section patients and to review the incidence of infections. The method used is a literature review. A total of eleven papers met the inclusion criteria for review. Based on the results of the article review, all of the research conducted were randomised controlled trial (RCT) studies. Randomised controlled trials (RCTs) are the gold standard for assessing the benefits of a treatment. Cefazolin, the first-generation cephalosporin antibiotic, is the most commonly used antibiotic for patients undergoing caesarean section. This aligns with the recommendations in the guideline. The highest prevalence of post-cesarean section infections is wound infections, with a percentage of 11.8% or 437 caesarean section patients. The most common microbiological pattern causing these infections is Staphylococcus aureus.